PENGARUH BENTUK SOAL DAN MOTIVASI SISWA TERHADAP KETERAMPILAN MEMBACA BAHASA JERMAN - Dwi Yoga Peny (Jurnal Evaluasi Pendidikan, 2017)
The purpose of this research is to identify the influence of test types and studentâ€™s motivation toward the German language achievement in Reading Comprehension Skill based on the learning achievement of the experiment and control group. The population of this research are Grade XII student of SMA Negeri 31 Jakarta. Research samples are students of grade XII IPA 1 and XII IPA 3 of SMA Negeri 31 Jakarta. Data are obtained by using random sampling. The research is conducted by using the â€œquasi experimentâ€ method with a â€œtreatment by levelâ€ design. Two ways ANOVA technique and â€œTukeyâ€ test are used to analyze the collected data. Before the data are analyzed, homogeneity and normality test are applied to see whether or not the data meet the requirement. The result of this research indicates that: (1) the different form of test (Short Answer and Multiple Choice) significantly influence the achievement of German language learning in terms of Reading Comprehension, (2) an interaction exists between the form of the test and studentâ€™s motivation and their achievement of learning German language, (3) a significant difference was present when Short Answer is applied to the group of students with high motivation, and Multiple Choice is given to other group of students, and (4) there is no difference between the group of students with low motivation to whom the Short Answer test is used and the group of students to whom Multiple Choice test is used.